2003
DOI: 10.1007/bf03405075
|View full text |Cite
|
Sign up to set email alerts
|

Literacy in Primary Care Populations

Abstract: Background: Almost half of Canadians experience difficulty using print media, according to the 1994 International Adult Literacy Survey. Our objectives were to estimate the prevalence of low-literacy patients in our practice, to determine whether reading grade level is associated with self-perceived health status in primary care, and to evaluate the reading difficulty of commonly used patient education pamphlets. Methods:We surveyed a random sample of 229 patients aged 18 to 85 years presenting for scheduled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…24 Smith and Haggerty note that poor literacy is an independent health risk; high-literacy users may be less dependent on health service interventions and more able to act on providers’ advice. 25 …”
Section: Discussionmentioning
confidence: 99%
“…24 Smith and Haggerty note that poor literacy is an independent health risk; high-literacy users may be less dependent on health service interventions and more able to act on providers’ advice. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Song’s [ 21 ] study among men with prostate cancer ( n = 1581), showed an association only with the mental component of quality of life. Finally, a study by Smith [ 22 ] conducted in a Canadian population of 259 adults in primary care, did not demonstrate an association between health literacy and quality of life. In light of these different results, it is possible that the relationship between health literacy and quality of life depends on certain aspects: specific chronic diseases, cultural characteristics or aspects of quality of life.…”
Section: Introductionmentioning
confidence: 89%
“…3 Fourth, much of the material used in physician practices in Canada for patient education may be written at a higher level than it ought to be. A recent study in a Montreal clinic, 5 for example, found that the average reading level of patient education materials in the practice was grade 11.5, higher than the recommended reading level of grade 7 or less.…”
Section: Irving Rootmanmentioning
confidence: 97%